The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1525/abt.2020.82.9.596
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Clay Modeling & Cat Cadaver Dissection on High School Students’ Outcomes & Attitudes in a Human Anatomy Course

Abstract: Increasing public concern over the use of animal dissection in education is driving development and testing of alternatives to animal use. Clay modeling has proven successful in achieving comparable or superior learning at postsecondary levels, but it has not yet been tested at secondary levels. This study tested the effectiveness and appeal of clay models vs. cat cadaver dissection in teaching human anatomy to high school students. Student performance on a content knowledge assessment increased following both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…However, without the right instructional aid the attainment of the objectives of teaching may not be successfully achieved (Okenyi, 2022;Olumorin et al, 2022). Previous studies have indicated that modelling clay is an effective teaching aid for facilitating learning through pedagogies that is based on cooperative approach (Grigg et al, 2020;Sanchez-Acevedo, M., & Kao, 2022). However, most existing literature did not consider the cognitive abilities of learners in consonance with their usage of modelling clay for knowledge construction.…”
Section: Discussionmentioning
confidence: 99%
“…However, without the right instructional aid the attainment of the objectives of teaching may not be successfully achieved (Okenyi, 2022;Olumorin et al, 2022). Previous studies have indicated that modelling clay is an effective teaching aid for facilitating learning through pedagogies that is based on cooperative approach (Grigg et al, 2020;Sanchez-Acevedo, M., & Kao, 2022). However, most existing literature did not consider the cognitive abilities of learners in consonance with their usage of modelling clay for knowledge construction.…”
Section: Discussionmentioning
confidence: 99%